Rethinking health systems in the context of urbanisation: Challenges from four rapidly urbanising low-income and middle-income countries - Elsey, Helen; Agyepong, Irene; Huque, Rumana; Quayyem, Zahidul; Baral, Sushil; Ebenso, Bassey; Kharel, Chandani; Shawon, Riffat Ara; Onwujekwe, Obinna; Uzochukwu, Benjamin; Nonvignon, Justice; Aryeetey, Genevieve Cecilia; et al. (BMJ Journals, 2022)
This article was published in the BMJ Global Health [© Author(s) (or their employer(s)) 2019. Re-use permitted under CC BY. Published by BMJ and the definite version is available at: http://dx.doi.org/10.1136/bmjgh-2019-001501 The Journal's website is at: https://gh.bmj.com/content/4/3/e001501.abstract